Pendampingan Pembuatan Nomor Induk Berusaha (NIB) Umkm Kerupuk Fajar Melalui Online Single Submission (OSS) - Furuhita, Fitri Aulia; Rizkiyah, Noor; Zuhri, Gideon Setyo Abuzar (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Micro, Small and Medium Enterprises or MSMEs are an important part of the economy of a region. MSME actors in Tlumpu Village, Sukorejo District, Blitar City are one of the urban villages that have a large number of MSMEs. There are various kinds of MSMEs in the Tlumpu Village, which vary widely in terms of products and services. One of the MSMEs in the Tlumpu Village is the Kerupuk Fajar MSME. MSME is a fairly large business and has been established since 2000. But UMKM Kerupuk Fajar does not yet have business legality. Therefore, Student Group 43 KKN-T MBKM UPN "Veteran" East Java provided assistance in making business legality as a form of community service in the Tlumpu Village. One type of business legality is the Business Identification Number (BIN). BIN registration is made online through the Online Single Submission (OSS) website. Group 43 KKN-T MBKM students applied several methods in this activity, namely surveys, discussions and mentoring. The assistance for making NIB was carried out at the Kerupuk Fajar MSME house. This assistance is carried out so that MSME actors will know better and provide results in the form of business licenses, so that MSME Kerupuk Fajar can run according to regulations set by the government